The second opinion [compact disc, unabridged] - Palmer, Michael, 1942-2013 (Brilliance Audio, 2009)
When her father, Petros, falls victim to a hit-and-run accident and is brutally injured, Dr. Thea Sperelakis struggles to assemble the facts regarding the accident, soon suspecting an attempt at homicide. Her father, serving as the only witness to the scene, must communicate to Thea through eye blinks, and what he reveals is horrifying.